Ecoframe: Transformasi UMKM Menuju Ekonomi Hijau dengan Pendekatan Akuntansi Hijau - Sura Klaudia; Nanda Kusumadewi; Retvina Eka Amin Nurjanah (Riset Manajemen dan Akuntansi, 2025)
MSMEs are a sector that contributes significantly to the Indonesian economy, yet most still employ conventional practices that neglect environmental impacts. The transition to a green economy requires MSMEs to adopt a record-keeping system that integrates financial and ecological aspects. This research developed and reviewed Ecoframe, a digital green accounting application designed to help MSMEs record financial transactions while simultaneously monitoring environmental indicators such as energy consumption, waste volume, and carbon emissions. Ecoframe consists of three main modules—Eco-Ledger, Eco-Dashboard, and Eco-Insight—that integrate recording, data visualization, and sustainability analysis into a single, integrated system. The application also features the EcoSync feature for data synchronization with national institutions, including the Financial Services Authority (OJK) and Statistics Indonesia (BPS), to support sustainability reporting and green fiscal policies.The study's findings indicate that Ecoframe offers significant potential in accelerating the transformation of MSMEs toward sustainable business practices, while addressing barriers such as low digital literacy, limited infrastructure, and limited understanding of green accounting. With its pentahelix approach and the Sahabat method, Ecoframe can serve as an innovative model that encourages MSMEs to improve efficiency, competitiveness, and environmental stewardship. This innovation supports the achievement of SDGs 8, 12, and 13 and strengthens Indonesia's green economy strategy.